TRANSFORMASI IDENTITAS VIRTUAL PRA DAN PASCA PERCERAIAN: ANALISIS KONTEN INSTAGRAM MICROCELEBRITY - Febriansyah Kulau; Awanis Akalili (MEDIAKOM, 2022)
Identity is a reflection of the reality of oneself. This reflection can be represented in the real world or the cyber world. But in cyberculture, the debate about real and virtual reality is a separate discourse. So that the identity represented in the cyber world is often referred to as a virtual identity. With the cyber world, identity is easy to transform, depending on the interests of the owner of the identity. This article will try to discuss the virtual identity transformation carried out by microcelebrity. The transformation is marked by the momentum of the divorce from the microcelebrity. Using qualitative content analysis, this article analyzes the uploads of two microcelebrity, namely Rachel Venya and Vicky Alaydrus on her Instagram. The findings of this article show that both Rachel Venya and Vicky Alaydrus experienced a virtual identity transformation after the divorce. But it was found that in this transformation, Vicky Alaydrus placed himself more as part of the microcelebrity than Rachel Venya. In the first few posts, Rachel Venya put herself as an individual without any soft selling that followed the reveal of her new virtual identity as a microcelebrity.